Comprehensive study on elementary school children’s 24-hours movement guidelines in physical education class - Dinafi, Yusra; Saputra, Adhe; Muzaffar, Ahmad (UIR Press, 2023)
Sedentary behavior changes during the pandemic caused a crucial reduction in the need for physical education and the time involved in physical activity so all parents and teachers at school experienced this challenge. The purpose of this study was to investigate the 24-hours movement guidelines, sleep quality, and screen time during and after the pandemic. This study used a cross-sectional method with an observational approach. The total subjects in this study were 1070 elementary school students with an average age of 10.69 ± 0.83 years, body weight 37.32 ± 10.57 kg, and height 139.66 ± 9.78 cm. The results showed that after the pandemic, children's playing habits outdoors and sleep duration increased sharply as the time in front of the screen decreased, although they tended to be the same as during the pandemic. Thus, it is hoped that these findings can serve as a reference for parents and teachers in schools to adopt a healthy lifestyle by prioritizing physical activity compared to using screens. so that habits during a pandemic can be overcome and students can improve their fitness levels. This investigation is limited to Jambi and its surrounding areas. Additional research can investigate the rise in the number of elementary school and respondents, as well as expand the scope to include the province, island, and country of Indonesia. This study findings may assist in restoring the physical activity behaviors of elementary school-aged children whose well-being is presently being compromised by excessive screen time, so that habits during a pandemic can be overcome and students can improve their fitness levels.